Regulation of the large (∼1000 kb) imprinted murine Ube3a antisense transcript by alternative exons upstream of Snurf/Snrpn - Landers, Miguel (Oxford University Press, 2004)
Most cases of Angelman syndrome (AS) result from loss or inactivation of ubiquitin protein ligase 3A (UBE3A), a gene displaying maternal-specific expression in brain. Epigenetic silencing of the paternal UBE3A allele in brain appears to be mediated by a non-coding UBE3A antisense (UBE3A-ATS). In human, UBE3A-ATS extends ∼450 kb to UBE3A from the small nuclear ribonucleoprotein N (SNURF/SNRPN) promoter region that contains a cis-acting imprinting center (IC). The concept of a single large antisense transcript is difficult to reconcile with the observation that SNURF/SNRPN shows a ubiquitous pattern of expression while the more distal part of UBE3A-ATS, which overlaps UBE3A, is brain specific. To address this problem, we examined murine transcripts initiating from several alternative exons dispersed within a 500 kb region upstream of Snurf/Snrpn. Similar to Ube3a-ATS, these upstream (U) exon-containing transcripts are expressed at neuronal stages of differentiation in a cell culture model of neurogenesis. These findings suggest the novel hypothesis that brain-specific transcription of Ube3a-ATS is regulated by the U exons rather than Snurf/Snrpn exon 1 as previously suggested from human studies. In support of this hypothesis, we describe U-Ube3a-ATS transcripts where U exons are spliced to Ube3a-ATS with the exclusion of Snurf-Snrpn. We also show that the murine U exons have arisen by genomic duplication of segments that include elements of the IC, suggesting that the brain specific silencing of Ube3a is due to multiple alternatively spliced IC-Ube3a-ATS transcripts.